[Uneasy peace ; The waiting game ; Life after politics [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
The result of the election and the possibility of a new coup is tackled out in this episode. Also features longtime politicians who lost in the election and are back to private practice.